Fortifikasi besi dan prebiotik pada kukis terhadap histologi usus tikus anemia - Rafika, Muhana; Lestari, Lily Arsanti; Helmyati, Siti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2023)
Iron dan prebiotic fortification in cookies towards intestine histology anemia ratsBackground: Anemia can also cause damage to small intestinal villous cells. Iron fortification can be an alternative prevention of anemia. Prebiotic additives can reduce the effects of fortification and improve intestinal villous.Objective: The study aims to determine the effect of breadfruit and soybean-based cookies with prebiotic and iron fortification on the small intestine's histology, especially the intestinal villous's height and width.Methods: Experimental study with posttest control group design with a total sample of 48 rats. Rats were divided into eight groups, given breadfruit and soybean-based cookies with the addition of FOS and NaFeEDTA (K1), FOS and FeSO4 (K2), FOS (K3), FeSO4 (K4), NaFeEDTA (K5), without fortification (K6). In addition, K- is a healthy mouse with standard feed, and K + is an anemia mouse. Anemia induction is for two weeks, and intervention is for 28 days. Intestinal histology was observed using an optilab microscope and measured using ImageRaster 4.0.5.Results: There were no significant differences in duodenum villous height, jejunum villous height, and ileum villous width (p>0.05). However, there were significant differences (p <0.05) for duodenum villous width (K- and K3), jejunum villous width (K1 and K4) and ileum villous height (K1, K2 and K +).Conclusions: Giving breadfruit-based and soybeans with prebiotic and iron fortification can increase the height and width of small intestinal villi.